SAFE EXECUTION OF TELECOMMUNICATION ENGINEERING WORKS IN KYRGYZSTAN AND THE UNITED STATES (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article examines issues of ensuring safety during the performance of telecommunication engineering work in the Kyrgyz Republic and the United States of America. Based on a comparative analysis of regulatory requirements, industry standards, and practical approaches, key differences were identified in the systems of personnel training, certification, and production process control. Special attention is given to OSHA, NWSA, and ANSI standards applied in the United States, as well as the current challenges in developing a similar regulatory framework in Kyrgyzstan. It is shown that the implementation of international standards, personnel training in risk-prevention methods, and the development of corporate safety systems help reduce injuries and improve the quality and sustainability of telecommunication projects.
Keywords: telecommunication works, occupational safety, industrial safety, OSHA, NWSA, ANSI, working at heights, RF safety, personnel certification, risk management, technical standards, Kyrgyzstan, USA.